Clarifying the spiritual values of forests and their role in sustainable forest management - Clark, William A. (Journal for the study of religion, nature and culture, 2011)
People value forests for many reasons. Historically, market and utilitarian values predominated both in forestry practice and the academic literature. Since the 1980s, forest professionals and researchers have given greater attention to less tangible forest values, including spiritual values. In reviewing the literature and searching the web, I found there is a broad awareness, but an overall lack of denition, of the spiritual value of forests. This lack of clarity hinders incorporating spiritual values into the practice of sustainable forest management. I attempt to clarify spiritual values as they apply to forests. Rather than viewing them as a single concept, I propose four broad categories of spiritual values as they relate to forests: intrinsic sacredness, associated sacredness (forests as the loci of significant spiritual history or culture), refection of God’s glory, and a place to experience transcendence.